Hindering and fostering factors SMEs performance in the Western Province of Sri Lanka - Kumarasinghe, Pivithuru Janak (International Journal of Management Excellence (ISSN: 2292-1648), 2017)
It is very significant to understand what factors affect the failure of Small and Medium Scale Industries (SMEs). The study is to empirically identify factors effecting on SMEs for the success and it’s an exploratory using a sample form Western province in Sri Lanka. To study the failure factors of SMEs in Western province in Sri Lanka., forty six (46) samples were selected through systematic random sampling throughout the year of 2010 to 2016. A questionnaire is used for collecting primary data for this study and it includes five point of Likert scale questions. Researcher gives more weight to failed ventures because this research main objective is find out factors affecting the rate of failure of small business enterprises. Reliability of dimensions is test using with the support of Cronbach’s Alpha Value. Validity of dimensions is test using convergent validity using KMO values. The results of the study revealed that out of eight factors affecting to failure such as Owner manager’s attitude, Financial Issues, Raw material availability, Labor Availability, Technology Issues, Entrepreneurial knowledge, Feasibility study and Government Support ; the raw material availability and the government support are the most important factors for the success.